Direct Arylation of Dipyrrolonaphthyridinediones Leads to Red‐Emitting Dyes with Conformational Freedom. Issue 4 (14th November 2017) - Sadowski, Bartłomiej; Rode, Michał F.; Gryko, Daniel T.
Abstract: A series of bis‐aryl dipyrrolonaphthyridinediones (DPNDs) with various substitution patterns have been designed and synthesized by direct arylation. This reaction occurs regioselectively at positions 3 and 9, which gives a straightforward entry to unique dyes that absorb in the red/far‐red region and emit in the far‐red/NIR region. The photophysical properties (absorption and fluorescence wavelength) can be controlled by altering the steric hindrance and electronic character of the peripheral aryl group. The fluorescence quantum yields are moderate in the majority of cases and almost independent of changes in the solvent polarity. DPNDs bearing substituents at the ortho position that prevent free rotation of the phenyl ring emit stronger fluorescence relative to the unhindered para analogues and, at the same time their absorption and emission bands are blueshifted. We have used computational methods to explain why electron‐donating substituents have significantly stronger effects than electron‐withdrawing substituents on the optical properties by invoking the electron‐accepting character of the DPND. Electrochemical measurements revealed that the HOMO and LUMO, as well as the electrochemical band gap, also depend strongly on the electronic character of the peripheral group. Abstract : Z‐Shaped, π‐expanded chromophores with a dipyrrolonaphthyridinedione core can be obtained by direct arylation. Despite having significant dihedral angles, the groups located on the aryl substituents have a profound effect on the optoelectronic properties of newly obtained dyes (see figure), which is revealed both experimentally and by computational studies.